Культурно-історичні епохи як текст у драматургії Лесі Українки - Турган, О. (Слово і Час, 2021)
У статті досліджуються особливості текстуалізації в драмах Лесі
Українки кодів культурно-історичних епох античності й середньовіччя, а також художнє втілення в античних та середньовічних образах
і мотивах світоглядних рис європейського й українського модернізму.
Розглядається специфіка переломлення характеристик українського буття межі XIX—XX ст. через призму названих епох у творах
«Іфігенія в Тавріді», «Кассандра», «Оргія», «Руфін і Прісцілла» та
«Камінний господар». Based on Lesia Ukrainka’s dramas “Iphigenia in Tavrida”, “Cassandra”, “The Orgy”, “Ruphin
and Priscilla”, and “The Stone Master”, the paper highlights peculiarities of cultural and historical
codes of the Antiquity and the Middle Ages in the writer’s works as well as literary
manifestation of the world-view features of European and Ukrainian Modernism in the antique
and medieval images and motifs.
Lesia Ukrainka reconsidered the heritage of archaic and late Antiquity, Hellenistic
period, Galilee at the time of Jesus, Early Christianity, and Medieval Spain. Each of these
epochs has its own dichotomy of social and biological phenomena, parameters of the world
model, and dominant fundamental points.
Lesia Ukrainka’s dramas transform the material of various cultural epochs, providing
polysemantic images that transfer the cosmos of a certain period into the neo-romantic and
neo-classical system of images and symbols. In the dramas, the writer raised the issues recurrent
in her works, such as love and sacrifice; beauty and ugliness; prophet, artist and ‘revolt
of the masses’; reality and dream; good and evil; truth and benefit; nostalgia for chivalry;
nostalgia for the Absolute; psychological and moral freedom and violence; spirit, soul, and
body; spiritual nobility and the rule of brutes; nature and culture, etc.
Numerous issues and characters, multifunctional ontological, cultural, and historical
phenomena, cultural codes, symbols, and mythologems acquire an existential meaning in
the author’s dramas fitting not only into various cultural contexts but also into the modern
reconsideration of mythopoetics.